Thailand’s Implementation from Entering the Members of United Nations Framework Convention on Climate Change 1992 - Kraithong, Nutjira; Poungjinda, Wachiraporn (Journal of Posthumanism, 2025)
The purposes of this research were to examine Thailand’s legislative and policy frameworks, identify gaps and challenges in the current approaches, and propose actionable recommendations for enhancing climate action strategies. The research findings revealed that Thailand’s journey since ratifying the United Nations Framework Convention on Climate Change (UNFCCC) in 1994 reflects a strong and evolving commitment to addressing the global climate crisis. Through participation in key international agreements namely the Kyoto Protocol and the Paris Agreement Thailand has laid a foundation for international collaboration, while also formulating comprehensive national policies such as the Climate Change Master Plan (2015–2050) and its Nationally Determined Contributions (NDCs). These efforts signify the country’s dedication to promoting low-carbon development, enhancing resilience, and aligning with Sustainable Development Goals (SDGs). Through interviews with policymakers, analysis of legal documents, and case studies, the article also provides an in-depth evaluation of Thailand’s strategies to mitigate and adapt to climate change.